Kajian Literatur: Penurunan Angka Kelahiran di Indonesia dan Implikasinya pada Keputusan Menikah - Abdullah Firman Gani (Yayasan Zia Salsabila, 2025)
This study aims to identify the factors causing the declining birth rate in Indonesia and its impact on marriage decisions. The method used is a literature review with a qualitative approach, analyzing secondary data from journals, articles, and other relevant sources. The results show that the declining birth rate is influenced by various factors, including increased education, changing social norms, economic conditions, and the “child free” phenomenon. Increased education, especially for women, encourages postponement of marriage for career and financial stability. Economic pressures, such as high living and education costs, are also the main reasons couples delay marriage. The “child free” phenomenon is increasingly accepted in modern culture, even though it goes against traditional values. The impact on Indonesia's demographic structure includes demographic bonus opportunities as well as challenges related to an aging population and the need for social services. The study concludes that the declining birth rate has significant implications for Indonesia's social, cultural and economic dynamics, requiring a holistic policy approach to manage demographic change in a sustainable manner.